The Influence Of Inflation, GDP Growth, Size, Leverage, And Profitability Towards Stock Price On Property And Real Estate Companies Listed In Indonesia Stock Exchange Period 2005-2013 - Herry Goenawan Soedarsa; Prita Rizky Arika (Bandar Lampung University, 2015)
This study aims to identify and analyze the effect of inflation, GDP growth, firm size, leverage and profitability towards the stock price on the property and real estate sectors listed in Indonesia Stock Exchange 2005-2013. The first hypothesis is the inflation rate influences negatively on the stock price, the second hypothesis is GDP growth influences positively on the stock price, the third hypothesis is the firm size influences positively on the stock price, the fourth hypothesis is leverage influences negatively on the stock price, and the fifth hypothesis is profitability influences positively on the stock price. Stock prices measured by the Annual Closing Price are seen in the company's annual financial statements.The sample of this study is the industrial property and the real estate listed in Indonesia Stock Exchange in 2005-2013. The sampling technique used is purposive sampling in order to obtain a total sample of 10 companies and real estate properties that meet the criteria established for research sample. Inflation is measured by the consumer price index rate, GDP growth is seen from the changes in nominal GDP, the size of the Company is measured by total sales, leverage is measured using the Debt Equity Ratio (DER) and profitability is measured by Return on Assets (ROA). Data analysis techniques is performed with the classical assumption, hypotheses are tested using multiple linear regression analysis using SPSS 18.0 for windows.The results showed that in partial inflation, GDP growth, and leverage have no effect on stock prices, while the size of the company and profitability have positive effect on the stock price on the company property and real estate sectors listed in Indonesia Stock Exchange.